SYNTHESIS, PHYSICOCHEMICAL ELUCIDATION AND BIOLOGICAL SCREENING STUDY OF NEW LIGAND DERIVED FROM 5,6-O-ISO PROPYLIDENE-L-ASCORBIC ACID AND ITS METAL(II) COMPLEXES - Al-Hasnawi, Fawzi; Lekaa Khalid Abdul Karem,; Duha Mohammed Mortatha, (Malaysian Journal of Science, 2023)
A simple chemistry method approach was used to synthesise new ligand derivate from L-ascorbic acid and its complexes. All of them were water-soluble and are used quite extensively in the medical and pharmaceutical fields. This study synthesised the new ligand derivative from L-ascorbic acid-base using the following steps: A 5,6-O-isopropylidene-L-ascorbic acid was prepared by reacting dry acetone with L-ascorbic acid followed by reacting it with trichloroacetic acid to yield [chloro(carboxylic)methylidene]-5,6-O-isopropylidene-L-ascorbic acid in the second stage. In the third stage, the derivative was reacted with (methyl(6-methyl-2-pyridylmethyl)amine to create a new ligand (ONMILA). This novel ligand was identified using a number of techniques, namely mass spectroscopy, 1H, 13C-Nuclear magnetic resonance, Fourier Transform Infrared (FT-IR), and Ultraviolet–visible (UV-Vis) spectra. It was observed that several complexes formed between the ligand and divalent metal ions (Co, Ni, Cu, Zn, Cd). Based on Micro Elemental Analysis, the mole ratio was (1:1) (M:L). Magnetic susceptibility, elemental analysis (C.H.N.O) procedures, molar conductivity tests, and proportion of metal ions calculations were used to describe the complexes. The findings showed the novel ligand had a mono, negative charge and behaved like a tridentate ligand type (N.N.O.). Therefore, the octahedral formula is suggested for all compounds. Only one spot was observed on thin layer chromatography (T.L.C.) for ligand (L) and complexes, indicating that the reaction completed and delivered only a single product. These chemicals have been connected to both Gram-negative and Gram-positive bacteria. The results suggested that antibacterial activity in metal complexes is higher than in the free ligand.